MODERN APPROACHES TO QUAIL NUTRITION: ENRICHED FEEDS AS A STRATEGY FOR ENHANCING MEAT PRODUCTIVITY - Dinara Zhanabayeva, Assel Paritova, Leila Sultanayeva, Dаnara Mussagiyeva, Yevgeniy Maier, Botagoz Aitkozhina, Dilora Senkebayeva, Nurlygul Yeleugaliyeva, Rakhimtay Tleulessov (Chelonian Research Foundation, 2024)
To enhance the meat productivity of quails, as well as to increase production volumes and improve the quality of poultry products, it is necessary to incorporate unconventional feed additives into the birds' diet. These additives promote the normalization of metabolic processes and improve nutrient digestibility. This article presents research findings on the meat productivity and nutritional value of Texan quail meat when using a compound feed enriched with the phytobiotic BioFeed-P and extruded corn. In the experimental group fed with the formulated compound feed, a 3.84% or 12.5 g advantage in live weight was observed by the end of the experiment. The absolute weight gain in the experimental group was 59.6±5.6 g, compared to 45.5 g in the control group. A notable advantage was also observed in the chemical composition of the meat, with the experimental group having a higher protein content of 21.89%. The fat percentage was slightly higher in the experimental group at 3.16%, with no significant differences in ash content between the groups. These findings are of interest to specialists in poultry farming and animal nutrition, and may prove valuable in formulating diets for fattening quails.